Investigation of the Influence of Particle Size on the Migration of DNAPL in Unsaturated Sand - Alazaiza, M. Y. D.; Ngien, S. K.; Bob, M. M.; Samira, A. Kamaruddin (CRC Press, 2016)
Four experimentswere conducted to investigate the migration of dense non-aqueous phase liquid (DNAPL) in unsaturated porous media using Light Reflection Method (LRM). The porous media was natural sand collected from a river and segregated into different sizes through sieving. Three different sizes of the sand were used in the first three experimentswhile the fourth experiment used a mixture of these sands.The sands were packed separately in rectangular acrylic columns and then DNAPL was injected from the top of the column. The migration of DNAPL, modeled by tetrachloroethylene (PCE), was observed using a digital camera connected to a laptop and controlled using special software. The images were captured according to a predetermined time interval set into the software. The results show a significant difference in the migration of PCE through these sands. The migration of PCE in Experiment 3 was much faster than the migration in the other experiments. This is most likely due to the large pores in the sand samples. Moreover, in the experiment using mixture sand, it was observed that the migration was uneven and relatively slower than other experiments. LRM provides a non-intrusive and non-destructive tool for studying fluid flow for which rapid changes in fluid flow in the entire flow domain is difficult to measure using conventional techniques.